2020
DOI: 10.3389/fonc.2020.01707
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Maintenance Associated Mutations in the Genetic Landscape of Gynecological Mucosal Melanoma

Abstract: Purpose Gynecological melanomas (GMs) are rare tumors with a poor prognosis. Here, we performed exome sequencing to generate the mutational landscape of GMs. Methods Next-generation sequencing was carried out on mucosal melanoma samples ( n = 35) obtained from gynecological sites. The alternative telomere lengthening (ALT) phenotype was verified by fluorescence in situ hybridization and the C-circle assay. Immunohist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
(43 reference statements)
1
6
0
Order By: Relevance
“…TERT is a gene encoding for the catalytic subunit of telomerase, which maintains telomeric integrity, ensuring cell immortality in human cancer [ 31 ]. Differently from CM, in which mutations occur mainly in the promoter region [ 32 ], the TERT alterations described in MM do not affect the promoter but consist in copy number variations, ultimately determining overexpression and stopping senescence [ 15 , 33 , 34 ]. ALK fusions, which are well-known tumors driven in lung adenocarcinomas, have been identified in ~11% of CMs, and, interestingly, MMs could also harbour such alterations [ 19 , 35 ].…”
Section: Biology and Genetic Alterationsmentioning
confidence: 99%
“…TERT is a gene encoding for the catalytic subunit of telomerase, which maintains telomeric integrity, ensuring cell immortality in human cancer [ 31 ]. Differently from CM, in which mutations occur mainly in the promoter region [ 32 ], the TERT alterations described in MM do not affect the promoter but consist in copy number variations, ultimately determining overexpression and stopping senescence [ 15 , 33 , 34 ]. ALK fusions, which are well-known tumors driven in lung adenocarcinomas, have been identified in ~11% of CMs, and, interestingly, MMs could also harbour such alterations [ 19 , 35 ].…”
Section: Biology and Genetic Alterationsmentioning
confidence: 99%
“…ATRX acts with the histone chaperone DAXX to insert histone variant H3.3 (Nandakumar et al, 2017; Pritchard, 2019), and loss of ATRX leads to increased homologous recombination facilitating telomere destabilization and alternative lengthening of telomeres (ALT; Abedalthagafi et al, 2013; Dyer et al, 2017; Marinoni et al, 2014; Yuan et al, 2020). LoF mutations (1.7%) and copy loss (HD: 0.8%, 0 %; LoH: 20%, 0 %) were observed in AM at a similar frequency to CM, but are slightly more common in MM (3.7%), where they are associated with tumors of the lower anatomy (Broit et al, 2021) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…ALT activation is described in sarcoma, astrocytoma, neuroblastoma, and carcinoma [ 18 ] cases as well as CM [ 16 ] and is related to functional loss of ATRX and/or histone H3.3 chaperone DAXX. In mucosal-melanoma-inactivating ATRX mutations can be revealed using immunohistochemistry [ 19 ]. In the current study ATRX loss was only found in (pre)malignant lesions and not in benign lesions.…”
Section: Discussionmentioning
confidence: 99%